2014
DOI: 10.14304/surya.jpr.v2n7.1
|View full text |Cite
|
Sign up to set email alerts
|

The Wnt/β-catenin Signaling Pathway in Epithelial Mesenchymal Transition

Abstract: Epithelial mesenchymal transition (EMT) is a well conserved process by which polarized, immotile epithelial cells transition into motile mesenchymal cells. EMT plays an important role during normal biological processes such as embryogenesis and wound healing. More recently, EMT has been studied for its role in cancer progression and metastasis. Understanding the molecular mechanisms that regulate EMT are key to developing novel therapeutic interventions for cancer. Dysregulated or uncontrolled activation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Canonical Wnt signaling is initiated by a WNT ligand, which is usually WNT7A or WNT3, and leads to the stabilization of CTNNB (b-catenin). Like Notch signaling, canonical Wnt signaling also causes GSK3b phosphorylation, allowing the accumulation and nuclear localization of SNAI1 and SNAI2 (Wu et al, 2012;Menezes, 2014). Further, the complex formed by CTNNB and TCF activates the transcription of many of the genes regulated by canonical Wnt signaling (Menezes, 2014), including SNAI2 (Conacci-Sorrell et al, 2003), TWIST1 (Howe et al, 2003), and ZEB1 (Sánchez-Tilló et al, 2011;Sanchez-Tillo et al, 2014).…”
Section: The Molecular Signaling Pathways Involved In Endmt Regulationmentioning
confidence: 99%
“…Canonical Wnt signaling is initiated by a WNT ligand, which is usually WNT7A or WNT3, and leads to the stabilization of CTNNB (b-catenin). Like Notch signaling, canonical Wnt signaling also causes GSK3b phosphorylation, allowing the accumulation and nuclear localization of SNAI1 and SNAI2 (Wu et al, 2012;Menezes, 2014). Further, the complex formed by CTNNB and TCF activates the transcription of many of the genes regulated by canonical Wnt signaling (Menezes, 2014), including SNAI2 (Conacci-Sorrell et al, 2003), TWIST1 (Howe et al, 2003), and ZEB1 (Sánchez-Tilló et al, 2011;Sanchez-Tillo et al, 2014).…”
Section: The Molecular Signaling Pathways Involved In Endmt Regulationmentioning
confidence: 99%
“…The regulatory effects of DAC and curcumin on cell migration were also investigated, and the results showed that either single or combination treatment with DAC and curcumin inhibited SKOV3 cell migration. One crucial EMT-associated gene, vimentin, is also a target gene of the Wnt/β-catenin signaling pathway 54 . Our results showed that not only vimentin, but also fibronectin, were down-regulated, whereas E-cadherin was up-regulated, by combined treatment with 5 μM DAC and 20 μM curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Wnt/β-catenin signaling is a classic pathway involved in modulating the development of cancer cells, i.e., proliferation, resistance, differentiation, motility, adhesion, and apoptosis of cancer cells [13]. However, several signal transducers that affect β-catenin activity (phosphorylation/degradation) are Glycogen Synthase Kinase 3β (GSK-3β), Axin, and adenomatous polyposis coli [9], [14].…”
Section: Introductionmentioning
confidence: 99%